Actively tunable weak and strong couplings in epsilon-near-zero ultrathin film-based Weyl semimetallic photonic crystals. (20th February 2023) - Sun, Mengran; Qian, Liming; Ye, Jingfei; Zheng, Gaige
Abstract: Lithography-free layered dielectric media plays an important role in photonic platforms and opens up new possibilities in the design of devices with large-scale compatibilities. In this work, we propose a hybrid structure consisting of phononic thin layer and Weyl semimetallic photonic crystals. Manipulation of electromagnetic waves and the interactions between different optical modes are presented, which is highly demanded for both fundamental research and practical applications. The weak and strong coupling effects result in hybrid polariton modes, of which the dispersion can be quantitatively described by a coupled harmonic oscillator model. In the Kretschmann coupling proposal, when the incident angle is smaller than the critical angle ( θ c = 25 ∘ ) of total internal reflection, a weak coupling is generated. However, when the incident angle is larger than θ c, anticrossing resluts from strong coupling can be observed. We believe that the use of easily manufactured WSM elements and the tunable hybridization of multiple optical modes will enable the manipulation of light-matter interactions with more flexibility in the mid-infrared range, and can significantly improve the functional properties of various devices.